Complications in Patients Undergoing Spinal Fusion After THA. Issue 2 (February 2018) - Diebo, Bassel G.; Beyer, George A.; Grieco, Preston W.; Liu, Shian; Day, Louis M.; Abraham, Roby; Naziri, Qais; Passias, Peter G.; Maheshwari, Aditya V.; Paulino, Carl B.
Abstract: Introduction: Patients with lumbar spine and hip disorders may, during the course of their treatment, undergo spinal fusion and THA. There is disagreement among prior studies regarding whether patients who undergo THA and spinal fusion are at increased risk of THA dislocation and other hip-related complications. Questions / Purposes: Is short or long spinal fusion associated with an increased rate of postoperative complications in patients who underwent a prior THA? Patients and Methods: A retrospective study of New York State's Department of Health database (SPARCS) was performed. SPARCS has a unique identification code for each patient, allowing investigators to track the patient across multiple admissions. The SPARCS dataset spans visit data of patients of all ages and races across urban and rural locations. The SPARCs dataset encompasses all facilities covered under New York State Article 28 and uses measures to further representative reporting of data concerning all races. Owing to the nature of the SPARCS dataset, we are unable to comment on data leakage, as there is no way to discern between a patient who does not subsequently seek care and a patient who seeks care outside New York State. ICD-9-Clinical Modification codes identified adult patients who underwent elective THA from 2009 to 2011. Patients who had subsequent spinal fusion (short: 2-3 levels, or long: ≥ 4 levels) with a diagnosis of adult idiopathic scoliosis or degenerative disc disease were identified. Forty-nine thousand nine hundred twenty patients met the inclusion criteria of the study. In our inclusion and exclusion criteria, there was no variation with respect to the distribution of sex and race across the three groups of interest. Patients who underwent a spinal procedure (short versus long fusion) had comparable age. However, patients who did not undergo a spinal procedure were older than patients who had short fusion (65 ± 12.4 years versus 63 ± 10.7 years; p < 0.001). Multivariate binary logistic regression models that controlled for age, sex, and Deyo/Charlson scores were used to investigate the association between spinal fusion and THA revisions, postoperative dislocation, contralateral THAs, and total surgical complications to the end of 2013. A total of 49, 920 patients who had THAs were included in one of three groups (no subsequent spinal fusion: n = 49, 209; short fusion: n = 478; long fusion: n = 233). Results: Regression models revealed that short and long spinal fusions were associated with increased odds for hip dislocation, with associated odds ratios (ORs) of 2.2 (95% CI, 1.4-3.6; p = 0.002), and 4.4 (95% CI, 2.7-7.3; p < 0.001), respectively. Patients who underwent THA and spinal surgery also had an increased odds for THA revision, with ORs of 2.0 (95% CI, 1.4-2.8; p < 0.001) and 3.2 (95% CI, 2.1-4.8; p < 0.001) for short and long fusion, respectively. However, spinal fusions were not associated with contralateral THAs. Further, short and long spinal fusions were associated with increased surgical complication rates (OR = 2.8, 95% CI, 2.1-3.8, p < 0.001; OR = 5.3, 95% CI, 3.8-7.4, p < 0.001, respectively). Conclusion: We showed that spinal fusion in adults is associated with an increased frequency of complications and revisions in patients who have had a prior THA. Specifically, patients who had a long spinal fusion after THA had 340% higher odds of experiencing a hip dislocation and 220% higher odds of having to undergo a revision THA. Further research is necessary to determine whether this relationship is associated with the surgical order, or whether more patient-specific surgical goals of revision THA should be developed for patients with a spinal deformity. Level of Evidence: Level III, therapeutic study